Analisis Hukum Atas Kecurangan (Fraud) Rumah Sakit Dalam Penyelenggaraan Jaminan Kesehatan Nasional: Legal Analysis of Hospital Fraud in The Implementation Of The National Health Insurance Program - Wicaksono, Emirza Nur; Khasanah, Dian Ratu Ayu Uswatun (Jurnal Hukum dan Etika Kesehatan, 2024)
Law enforcement against fraud committed by hospitals in the implementation of the National Health Insurance (JKN) program is a crucial aspect in maintaining the integrity of the healthcare system in Indonesia. This study aims to analyze the legal framework governing hospital fraud and to assess the effectiveness of its implementation in practice. The research method used is normative with a statute approach and conceptual approach. The results of the study show that law enforcement regarding hospital fraud in the JKN program has been regulated by existing legislation. However, its implementation still faces several challenges. The current legal regulations are not fully effective in preventing and addressing fraud. Implementation is hindered by various obstacles, including a lack of coordination among law enforcement agencies, weak internal oversight, and minimal strict sanctions against fraud perpetrators. The conclusion of this study is that law enforcement on hospital fraud within the JKN program requires more effective and efficient efforts, as well as increased awareness and compliance with the applicable laws and regulations.